2017
DOI: 10.1007/s10147-017-1213-z
|View full text |Cite
|
Sign up to set email alerts
|

Selecting patients for hyperthermia combined with preoperative chemoradiotherapy for locally advanced rectal cancer

Abstract: Hyperthermia might selectively enhance the preoperative treatment response in LARC with positive CA9 expression and offset the negative effect of hypoxia on prognosis. Pretreatment evaluation of hypoxia could aid in the selection of patients who might benefit from hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…75 Moreover, several studies have also demonstrated a better local control rate and survival benefit of the combination of preoperative neoadjuvant chemoradiotherapy and hyperthermia than chemoradiotherapy alone for rectal cancer patients. 76,77…”
Section: Clinical Use Of Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…75 Moreover, several studies have also demonstrated a better local control rate and survival benefit of the combination of preoperative neoadjuvant chemoradiotherapy and hyperthermia than chemoradiotherapy alone for rectal cancer patients. 76,77…”
Section: Clinical Use Of Hyperthermiamentioning
confidence: 99%
“…75 Moreover, several studies have also demonstrated a better local control rate and survival benefit of the combination of preoperative neoadjuvant chemoradiotherapy and hyperthermia than chemoradiotherapy alone for rectal cancer patients. 76,77 In clinical practice, RHT combined with radiochemotherapy has been shown to be an effective sensitizer for chemoradiotherapy, which can be applied in various types of tumors. Chemoradiotherapy is carried out according to clinical guidelines, while hyperthermia is usually performed immediately after RT, once or twice a week.…”
Section: Hyperthermia Combined With Chemoradiotherapymentioning
confidence: 99%